PROGRAM OF STATE SUPPORT TO AGRICULTURAL CREDITING - Vojinović, Željko; Zelenović, Vera; Cvijanović, Drago (Economics of Agriculture, 2017)
One of the most important industries in Serbia are agriculture, the potential for the State, which is on its way to become a member of the European Union, represents the backbone of economic growth and development. Integrating with the EU represents a task to establish such a model and framework of relations of the State towards agriculture in order to easier harmonization of national policies with the policy of the EU. In this day and age when growing awareness about the importance of nutrition and the importance of the arable land, it is necessary to devote special attention to the problem of the lack of funds in the framework of agricultural production. A solution to the problem of technical and technological processes in the manufacture of food products, especially healthy food, you can browse in the measures of improving and increasing production through different approaches to stimulate and subsidizing of agricultural producers. It is certainly in the interest of the State, so it is for that reason necessary to devote special attention to budget and how fnancing and other measures in the direction of the stimulus of all participants in the market who participate in agricultural production.